Supplement to the knowledge of ptyctimous mites (Acari, Oribatida) from Palaearctic Region - Niedbała, Wojciech (Zootaxa, 2015)
A list of over 400 new localities studied for ptyctimous mites within Palaearctic Region and a list of 96 identified species of ptyctimous mites of 20 genera are given. The species, knowledge of whose zoogeographical ranges was extended, have been pointed out. One new species, Phthiracarus pachys sp. nov. from Spain, is described. A few rare species have been diagnosed and their additional morphological data are given. The species from a few papers that have not been included in the monograph by Niedbała (2011) are commented on. The unjustified recombinations of species between certain genera (Subías 2004, updated in 2015) and unaccepted proposals on synonymy of some species by Subías & Shtanchaeva (2011) have been commented on.